Advantages of Chinese herbal medicine in treating rheumatoid arthritis: a focus on its anti-inflammatory and anti-oxidative effects - Wang, Xiaoyu; Kong, Youqian; Li, Zeguang (Frontiers in Medicine, 2024)
Oxidative stress is a condition characterized by an imbalance between the oxidative and antioxidant processes within the human body. Rheumatoid arthritis (RA) is significantly influenced by the presence of oxidative stress, which acts as a pivotal factor in its pathogenesis. Elevated levels of mitochondrial reactive oxygen species (ROS) and inflammation have been found to be closely associated in the plasma of patients with RA. The clinical treatment strategies for this disease are mainly chemical drugs, such as nonsteroidal anti-inflammatory drugs (NSAIDs), disease-modifying anti-rheumatic drugs (DMARDs), glucocorticoids (GCs) and biological agents, but it is difficult for patients to accept long-term drug treatment and its side effects. In the theory of traditional Chinese medicine (TCM), RA is thought to be caused by the attack of "wind, cold, damp humor", and herbs with the effect of removing wind and dampness are used to relieve pain. Chinese herbal medicine boasts a rich heritage in effectively attenuating the symptoms of RA, and its global recognition continues to ascend. In particular, RA-relevant anti-inflammatory/anti-oxidative effects of TCM herbs/herbal compounds. The main aim of this review is to make a valuable contribution to the expanding pool of evidence that advocates for the incorporation of Chinese herbal medicine in conventional treatment plans for RA.